DOES MICRORNA-140 PLAY A ROLE IN THE DEVELOPMENT AND PROGRESSION OF OESOPHAGEAL SQUAMOUS CELL CARCINOMA? - A SYSTEMATIC REVIEW. - April, Johannes; Simba, Hannah; Moodley, Yoshan (Student's Journal of Health Research Africa, 2024)
Background Oesophageal squamous cell carcinoma (OSCC) is one of the most common and lethal cancers worldwide. Despite advances in treatment, the five-year survival rate for OSCC remains suboptimal. Recent studies reveal that microRNAs (miRNAs) are involved in developing and progressing various types of cancer. Therefore, the modulation of miRNAs could have implications for new OSCC treatments. The purpose of this research was to summarise the published evidence on the impact of miRNA-140 on OSCC development and progression. Methods PubMed and Scopus were searched for the relevant literature. Study inclusion criteria were: basic science studies published during 1 June 2014–1 June 2023. Study exclusion criteria were: research without an appropriate analysis, non-English language publications, and grey literature. No study quality assessment tool currently exists for basic science studies, and all studies that met the eligibility criteria were incorporated in the review. The literature search results were analyzed with descriptive statistics (frequencies, percentages) and presented as a narrative synthesis. Results Eight papers were included in this review. All included studies were from China, and ECA109 was the most common OSCC cell line used (8 studies, 100%). Findings from studies involving transfection of OSCC cell lines with miRNA-140 mimics suggest that increased levels of miRNA-140 impair OSCC development and progression. Several genes appear to be regulated by miRNA-140 in OSCC development and progression (NFYA, ZEB1 & 2, ErbB4, and NRIP1). Hypoxia reduces miRNA-140 levels, thereby promoting OSCC development and progression. High levels of miRNA-140 were found to confer resistance to platinum-based chemotherapy drugs. Conclusion miRNA-140 plays multiple roles in the development and progression of OSCC, including influencing tumorigenesis, apoptosis of tumor cells, genome instability, invasion, metastasis, and chemotherapy resistance. Recommendation More research is needed to extend and validate these results, and to develop OSCC therapies aimed at modulating miRNA-140.